«Global Landscapes» in Small Places: the Linguistic Picture behind the Public Inscriptions in Veliko Тurnovo - Atanassova, S. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
This article analyzes the language landscape of the inscriptions in the public space of Veliko Tarnovo, Bulgaria. Despite the fact that there is only one official language in the country – Bulgarian, the inscriptions reveal a diverse use of different languages. The use of foreign languages (primarily English is used as the language of international communication) can be direct, but more often «parallel use» occurs. «Parallel use» is the use of Bulgarian and foreign languages and is observed both in the form of translation and a mixture of languages. The confusion of languages leads to a creative linguistic use and unexpected interpretations. The analysis shows that such factors as sub-diversity, globalization and mobility of the population are characteristic not only of megacities and cosmopolitan urban centers, but also of smaller settlements.